A porous medium approach to the 3D modelling of an entire rotating packed bed for post-combustion carbon capture. (15th June 2023) - Zhang, Guojun; Ma, Lin; Pourkashanian, Mohamed
Highlights: A novel full 3D Eulerian porous medium model is developed for the CO2 capture process in a RPB. The hydrodynamics, thermodynamics and chemical-enhanced mass transfer in the RPB are effectively and accuartely analyzed. The mass transfer in the packing region and outer cavity zone is quantitatively evaluated under various operating conditions. The model paves the way for scaling up and process optimization of RPBs for industrial post-combustion carbon capture. Abstract: Rotating packed bed (RPB) technology shows great potential for post-combustion capture. However, the capture process inside the full RPB is difficult to simulate, due to the complexity of the process and the neglect of the CO2 capture in the outer cavity zone. In this paper, a full 3D CFD model, including the packing and the inner and outer cavity zones, has been established employing the Eulerian porous medium method coupled with various sub-models. The CO2 capture performance in the packing and outer cavity zones has been quantitatively analyzed under different operating conditions. The simulation results show good agreement with the experimental data, and the contribution of the outer cavity zone to the CO2 capture of the RPB is in the range of 28 %∼42 %. This work provides a new approach to efficiently simulate the mass transfer process in the RPB.